Advance Pumping Technologies for Sustainable Bio Energy Systems: A Review of Efficiency Metrics and Integration Strategies - Perera, Hasith; hosan, shen; wijesekara, dasith; vithanage, vimukthi; sbeysinghe, shakya; koswattage, kaveenga (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2025)
The paper presents a systematic review of the pump technologies in industrial sectors by comparing the data on operational performance and case studies. Three types of pumps were considered, namely, positive displacement (rotary, reciprocating, linear), kinetic (axial flow, centrifugal, submersible), and special (vacuum, jet, peristaltic). The approach included literature review on technical specifications, evaluation of literature on the field performance of the pumps in industrial functions, and comparative evaluation of the pump selection criteria in the industries such as oil and gas, chemical processing, pharmaceuticals, mining, and bioenergy. It has been shown that positive displacement pumps are effective in high-viscosity flows more than 10,000 cP, and screw pumps are the most efficient with 80-95% efficiency covering the widest viscosity (1 to 10¹⁰ cP). The pressure capacity of reciprocating systems was excellent and plunger pumps were made to a pressure of up to 1,000 bar with low leakage rates of 0.1-0.5%. The most effective pumps were kinetic pumps that were suitable in high flow applications and in the case of axial flow systems that operated on a volume of up to 80,000 L/min. Positive displacement pumps were necessary in the bioenergy processes to transport biomass and digestate and centrifugal pumps to manage biogas condensate in the best way. This analysis results in the development of the evidence-based selection framework that allows operational cost savings of 15-30% due to the increase in the efficiency to the same extent and the achievement of completion of bioenergy process efficiency by 12%. These results give practical recommendations on how to maximize the choice of fluid transport systems in various industrial uses.